The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1093/femspd/ftv046
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the platelet activating factor signaling pathway to cerebral microcirculatory dysfunction during experimental sepsis by ExoU producingPseudomonas aeruginosa

Abstract: Intravital microscopy was used to assess the involvement of ExoU, a Pseudomonas aeruginosa cytotoxin with phospholipase A2 activity, in dysfunction of cerebral microcirculation during experimental pneumosepsis. Cortical vessels from mice intratracheally infected with low density of the ExoU-producing PA103 P. aeruginosa strain exhibited increased leukocyte rolling and adhesion to venule endothelium, decreased capillar density and impaired arteriolar response to vasoactive acetylcholine. These phenomena were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…A variety of potent lipid mediated receptor inhibitors, including BN52021 and WEB2086, have been characterized2029 and shown to have therapeutic potential in a number of neurological disorders, including models of ischemia-reperfusion injury30, neuroinflammatory disease31, neurotoxic injury32. PAFR inhibitors display neuroprotective properties after TBI33343536 and these compounds might exert their effects via an inhibitory mechanism involving the interaction between PAF and PAFR3738. Our studies have demonstrated that PAFR inhibitors caused a reduction in PAF release resulting in a down regualtion of TBI induced inflammatory cytokines394041 in animal models of brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of potent lipid mediated receptor inhibitors, including BN52021 and WEB2086, have been characterized2029 and shown to have therapeutic potential in a number of neurological disorders, including models of ischemia-reperfusion injury30, neuroinflammatory disease31, neurotoxic injury32. PAFR inhibitors display neuroprotective properties after TBI33343536 and these compounds might exert their effects via an inhibitory mechanism involving the interaction between PAF and PAFR3738. Our studies have demonstrated that PAFR inhibitors caused a reduction in PAF release resulting in a down regualtion of TBI induced inflammatory cytokines394041 in animal models of brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, it has become apparent that inflammation triggered by systemic infections can negatively impact the brain and two recent studies used IVM to examine these changes after bacterial sepsis . Plotkowski et al .…”
Section: Systemic Infectionsmentioning
confidence: 99%
“…Notably, it has become apparent that inflammation triggered by systemic infections can negatively impact the brain and two recent studies used IVM to examine these changes after bacterial sepsis . Plotkowski et al . used a Pseudomonas aeruginosa pneumonia model of sepsis and observed significant leukocyte rolling and adhesion to the cerebral vessels accompanied by impaired capillary perfusion in the brain.…”
Section: Systemic Infectionsmentioning
confidence: 99%
See 2 more Smart Citations